CP-080 Clinical pharmacy in rheumatology ward: 5 month activity report. (25th February 2017) - Cousin, T; Saucez-Duquesne, MO; Mallémont, A; Giuliani, C; Parrein, P; Chenailler, C; Vittecoq, O; Varin, R
Abstract : Background: Several clinical pharmacy activities (CPA) were implemented in the rheumatology ward between March and April 2016: medical reconciliation at admission (MRA) and pharmaceutical analysis of prescriptions (PAP) for each patient at admission and then weekly. Purpose: These CPA set up a strong link between the hospital and post-discharge sectors to ensure medicine continuity and to improve the quality of care of patients and avoid medical errors. Material and methods: A pharmaceutical team (one resident and two interns) allowed quick and efficient implementation of these CPA. For the MRA, the pharmaceutical team performed a medication history prior to patient admission using several information sources (medical file, pharmacist, general physician, patient himself) to form the optimised medical report (OMR). Then, the admission script was compared with the OMR, and medical discrepancies (MD) were detected. Pharmacists and physicians analysed the MD to determine those to be documented or corrected. A level 3 PAP (according to the French Society of Clinical Pharmacy) was also performed by the pharmacy resident. Results: 269 patients were admitted to the rheumatology ward between May and September 2016 (host capacity: 18 patients). 269 MRA (100% of admissions) were performed. 100 unintended MD were detected among 1934 MD and had mainly a 'significant clinical impact' (90%) according to the Hatoum Scale. 430 PAP were performed and 77 pharmaceutical interventions (PI) were made (1 PI every 9 prescriptions). Posology and treatment schedule were the most frequent types of PI (49%) and medicines from the 'N' ATC code ('nervous system') were mainly involved in these PI (68%). Conclusion: Over these first 5 months of activity, unintended MD and PI have decreased. We can therefore assume that pharmacists are useful in clinical departments and these APC have to be kept. Furthermore, we can improve the quality and safety of care and reinforce the link between hospital and post-discharge sectors by setting up medical reconciliation at hospital discharge. No conflict of interest